Method for regulating and controlling columnar crystal structure characteristics of rapidly-solidified multi-principal-element molybdenum-niobium-tungsten alloy

By performing high-temperature annealing of the multi-main molybdenum niobium tungsten alloy, the problem of excessive grain size in its columnar crystal structure is solved, grain refinement and tissue optimization are achieved, and the performance and stability of the material are improved.

CN119162516APending Publication Date: 2024-12-20NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535557.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The columnar crystal structure formed by multi-main refractory alloys is large in size when they are fast solidified, and it is difficult to refine them through traditional methods, affecting the structure state and performance of the material.

Method used

By performing high-temperature annealing on the solidified columnar crystal structure alloy material, the sub-grain boundaries within the alloy grains are moved, thereby decomposing them into multiple small grains with small orientation differences, reducing the grain size and texture degree. The specific steps include heating to 1700-1900°C in a vacuum high-temperature annealing furnace for 4 h-6 h, controlling the temperature increase rate to 10°C/min to 20°C/min and the vacuum degree is 5.0×10-3Pa to 5.0×10-5Pa.

Benefits of technology

It effectively reduces the grain size and texture degree of columnar crystal structure alloy materials, so that their performance is basically the same in all directions, making it convenient for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162516A_ABST
    Figure CN119162516A_ABST
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling columnar crystal structure characteristics of a rapidly solidified multi-principal-element molybdenum-niobium-tungsten alloy, which comprises the following steps: step 1, placing a multi-principal-element molybdenum-niobium-tungsten liquid alloy in a crucible for solidification to form a columnar crystal structure alloy material; and secondly, the columnar crystal structure alloy material formed in the first step is placed in a vacuum high-temperature annealing furnace, the temperature is increased to 1700-1900 DEG C after vacuumizing is conducted, heat preservation is conducted for 4-6 h, and then furnace cooling is conducted. According to the method, the solidified columnar crystal structure alloy material is subjected to high-temperature annealing treatment, so that sub-grain boundaries in alloy grains move and are decomposed into a plurality of small grains with small orientation differences, at the moment, small-angle grain boundaries do not obviously grow up, the grain size and the texture degree are finally reduced, and the strength of the alloy material is improved. The method is suitable for the technical field of multi-principal-element refractory alloy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of multi-principal component refractory alloy materials, and in particular relates to a method for regulating and controlling columnar crystal structure characteristics of a rapidly solidified multi-principal component molybdenum-niobium-tungsten alloy. Background Art

[0002] Multi-principal refractory alloys have ultra-high strength and have become one of the research hotspots in the field of materials since their introduction. When multi-principal refractory alloys are smelted in a water-cooled copper crucible, columnar crystal structures are generally formed due to the fast solidification rate. However, the grain size of columnar crystal structures is usually very large, which is not the desired organizational state for material preparation.

[0003] When multi-principal component refractory alloys are used as casting materials, it will not be possible to refine the grains and optimize the microstructure through pressure processing such as extrusion and forging. For traditional single-principal component alloy materials, when faced with the problem of coarse grains in casting, the microstructure can usually be optimized by adjusting the solidification technology and alloy chemical composition. For multi-principal component refractory alloys, adjusting the solidification technology and alloy chemical composition is also an important method to regulate its solidification microstructure and refine the grains. However, multi-principal component refractory alloys cannot be transplanted into new alloy systems because their composition is more complex and the role of doping elements is different for alloys of different systems. In addition, although the use of adjusted solidification technology can regulate the solidification microstructure characteristics of the alloy, the effect is relatively limited and has high performance requirements for solidification equipment.

[0004] Therefore, it is urgent to develop a method that can regulate the columnar crystal structure characteristics of rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a method for regulating the characteristics of columnar crystal structure of rapidly solidified multi-principal molybdenum-niobium-tungsten alloy. The method performs high-temperature annealing on the solidified columnar crystal structure alloy material to move the subgrain boundaries in the alloy grains, thereby decomposing into a plurality of small grains with small orientation differences. At this time, the small-angle grain boundaries have not yet grown significantly, and finally the grain size and texture degree are reduced, thereby solving the problem of large grain size and poor organizational state of columnar crystal structure of multi-principal refractory alloy.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for regulating the columnar crystal structure characteristics of a rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy, characterized in that the method comprises the following steps:

[0007] Step 1: placing a multi-principal element molybdenum-niobium-tungsten liquid alloy in a crucible and solidifying it to form a columnar crystal structure alloy material;

[0008] Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high-temperature annealing furnace, evacuate the vacuum, heat it to 1700-1900° C., keep it warm for 4 h-6 h, and then cool it with the furnace.

[0009] The above-mentioned method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy is characterized in that the multi-principal element molybdenum-niobium-tungsten liquid alloy in step one includes the following components with atomic contents: Mo 30% to 35%, Nb 30% to 35%, and W 30% to 35%.

[0010] The above-mentioned method for regulating the columnar crystal structure characteristics of rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy is characterized in that the grain state of the columnar crystal structure alloy material in step one is one or more of columnar, blocky and ellipsoidal.

[0011] The above-mentioned method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy is characterized in that the vacuum in step 2 is evacuated to a vacuum degree of 5.0×10 -3 Pa~5.0×10 -5 Pa, and the heating rate is 10°C / min to 20°C / min.

[0012] The present invention controls the heating rate to be 10°C / min to 20°C / min to avoid excessive heating rate, which may cause serious deformation of the multi-principal molybdenum-niobium-tungsten alloy material under the influence of heat. Meanwhile, excessively slow heating rate may greatly extend the heating time, resulting in cost waste. By controlling the vacuum degree to be 5.0×10 -3 Pa~5.0×10 -5 Pa is used to prevent the multi-element molybdenum-niobium-tungsten alloy from oxidizing at high temperatures.

[0013] The above-mentioned method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy is characterized in that the crucible in step one is a water-cooled copper crucible.

[0014] The above-mentioned method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy is characterized in that the initial temperature of the water-cooled copper crucible is 5°C to 20°C.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. The present invention performs high temperature annealing on the solidified columnar crystal alloy material to move the subgrain boundaries in the alloy grains, thereby decomposing them into multiple small grains with small orientation differences. At this time, the small-angle grain boundaries have not yet grown significantly, reducing the grain size and texture. In the past, the regulation of alloy solidification structure characteristics mainly controlled the solidification technology and changed the alloy composition, and there has been no process method for annealing to control the columnar crystal structure characteristics of multi-principal alloys.

[0017] 2. The multi-principal component solidifying alloy of the present invention has a "lattice distortion effect" and a "hysteresis diffusion effect". The various elements in the multi-principal component solidifying alloy are randomly distributed, resulting in irregular arrangement of atoms in the lattice, thereby producing lattice distortion. Storing more distortion in the solidifying alloy can form a higher proportion of subgrain boundaries. These subgrain boundaries merge and grow during the annealing process, decomposing large grains into multiple small grains, thereby reducing the grain size. The multi-principal component solidifying alloy contains a variety of elements, and the activities of these elements are different and the lattice distortion is serious. When competing for the same vacancies, it will lead to diffusion difficulties, showing a hysteresis diffusion effect, which helps to maintain the high-temperature stability of the multi-principal component solidifying alloy and does not form new phases. At the same time, under high temperature conditions, small-angle grain boundaries can avoid the adverse effects of rapid coarsening and maintain good organizational stability. Therefore, during the high-temperature annealing process, only the subgrain boundaries of the multi-principal component solidifying alloy merge and grow, while the small-angle grain boundaries do not merge and grow, which ultimately causes the alloy grain size to decrease.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the IPF diagram of the columnar crystal structure alloy material before annealing in Example 1 of the present invention.

[0020] Figure 2 This is the IPF diagram of the columnar crystal structure alloy material after annealing in Example 1 of the present invention.

[0021] Figure 3 This is a grain boundary analysis diagram of the columnar crystal structure alloy material before annealing in Example 1 of the present invention.

[0022] Figure 4 This is a grain boundary analysis diagram of the columnar crystal structure alloy material after annealing in Example 1 of the present invention.

[0023] Figure 5 1 is the {111} crystal plane pole figure of the columnar crystal structure alloy material before annealing in Example 1 of the present invention.

[0024] Figure 6 It is the {111} crystal plane pole figure of the columnar crystal structure alloy material after annealing in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] Example 1

[0026] The method of this embodiment includes the following steps:

[0027] Step 1: placing a multi-principal molybdenum-niobium-tungsten liquid alloy in a water-cooled copper crucible at 5° C. to solidify to form a columnar crystal structure alloy material; the multi-principal molybdenum-niobium-tungsten liquid alloy comprises the following atomic contents: Mo 33.3%, Nb 33.3%, W 33.3%;

[0028] Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high temperature annealing furnace and evacuate to a vacuum degree of 5.5×10 -3 Pa, and heated to 1800°C at a rate of 17.5°C / min, and kept at that temperature for 4 h, and then cooled with the furnace.

[0029] After testing, it was found that the grain state of the columnar crystal structure alloy material of this embodiment was columnar and ellipsoidal.

[0030] The grain size and texture degree of the columnar crystal structure alloy material before and after annealing in this embodiment are analyzed by EBSD technology. Figure 1 and Figure 2 As shown in the figure, the average grain size of the columnar crystal alloy material before annealing is about 300μm, while the average grain size after annealing is reduced to 200μm, indicating that the grain size of the columnar crystal alloy material can be reduced by high temperature annealing; Figure 3 and Figure 4 As shown in the figure (red indicates subgrain boundaries of 0.4° to 2°, blue indicates small-angle grain boundaries of 2° to 15°, and black indicates grain boundaries greater than 15°), the subgrain boundary content of the columnar crystal structure alloy material before annealing accounts for 50.4%, and the small-angle grain boundary content accounts for 4%, while the subgrain boundary content after annealing is reduced to 35%, and the small-angle grain boundary content is increased to 8.8%, indicating that the subgrain boundaries inside the columnar crystal structure alloy material have moved, resulting in changes in the content of grain boundaries at different angles; Figure 5 and Figure 6 As shown in the figure, before annealing, the poles of the {111} crystal plane pole figure are concentrated, with a maximum pole density of 5.06, while after annealing, the poles of the {111} crystal plane pole figure are more evenly distributed, with a maximum pole density of only 2.11, indicating that the texture degree of the columnar crystal structure alloy material is reduced.

[0031] In summary, the present invention performs high temperature annealing on the columnar crystal structure alloy material, which effectively reduces the grain size and texture degree, and can make the performance of the columnar crystal structure alloy material basically the same in all directions, which is convenient for engineering applications.

[0032] Example 2

[0033] The method of this embodiment includes the following steps:

[0034] Step 1: placing a multi-principal molybdenum-niobium-tungsten liquid alloy in a water-cooled copper crucible at 20° C. to solidify to form a columnar crystal structure alloy material; the multi-principal molybdenum-niobium-tungsten liquid alloy comprises the following atomic contents: Mo 30%, Nb 35%, W 35%, and the grain state of the columnar crystal structure alloy material is blocky;

[0035] Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high temperature annealing furnace and evacuate to a vacuum degree of 5.5×10 -5 Pa, and heated to 1700°C at a rate of 10°C / min, and kept at that temperature for 5 h, and then cooled with the furnace.

[0036] After testing, it is found that the grain state of the columnar crystal structure alloy material in this embodiment is blocky; the average grain size of the columnar crystal structure alloy material before annealing in this embodiment is about 312μm, and the average grain size is reduced to 205μm after annealing, indicating that the grain size of the columnar crystal structure alloy material can be reduced after high temperature annealing.

[0037] Example 3

[0038] The method of this embodiment includes the following steps:

[0039] Step 1: placing a multi-principal molybdenum-niobium-tungsten liquid alloy in a water-cooled copper crucible at 12° C. to solidify to form a columnar crystal structure alloy material; the multi-principal molybdenum-niobium-tungsten liquid alloy comprises the following atomic contents: Mo 35%, Nb 30%, W 35%;

[0040] Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high temperature annealing furnace and evacuate to a vacuum degree of 7.0×10 -3 Pa, and heated to 1850°C at a rate of 12°C / min, and kept at that temperature for 4 h, and then cooled in the furnace.

[0041] After testing, it is found that the grain state of the columnar crystal structure alloy material in this embodiment is columnar and blocky; the average grain size of the columnar crystal structure alloy material before annealing in this embodiment is about 308μm, and the average grain size is reduced to 209μm after annealing, indicating that the grain size of the columnar crystal structure alloy material can be reduced after high temperature annealing.

[0042] Example 4

[0043] The method of this embodiment includes the following steps:

[0044] Step 1: placing a multi-principal molybdenum-niobium-tungsten liquid alloy in a water-cooled copper crucible at 8° C. to solidify to form a columnar crystal structure alloy material; the multi-principal molybdenum-niobium-tungsten liquid alloy comprises the following atomic contents: Mo 35%, Nb 35%, W 30%;

[0045] Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high temperature annealing furnace and evacuate to a vacuum degree of 7.0×10 -4 Pa, and heated to 2000°C at a rate of 20°C / min, and kept at that temperature for 6 h, and then cooled with the furnace.

[0046] After testing, it is found that the grain state of the columnar crystal structure alloy material in this embodiment is ellipsoidal; the average grain size of the columnar crystal structure alloy material before annealing in this embodiment is about 322μm, and the average grain size is reduced to 213μm after annealing, indicating that the grain size of the columnar crystal structure alloy material can be reduced after high temperature annealing.

[0047] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for regulating the columnar crystal structure characteristics of a rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy, characterized in that: The method comprises the following steps: Step 1: placing a multi-principal element molybdenum-niobium-tungsten liquid alloy in a crucible and solidifying it to form a columnar crystal structure alloy material; Step 2: Place the columnar crystal structure alloy material formed in step 1 in a vacuum high-temperature annealing furnace, evacuate the vacuum, heat it to 1700° C. to 1900° C., keep it warm for 4 h to 6 h, and then cool it with the furnace.

2. The method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy according to claim 1 is characterized in that: The multi-principal element molybdenum-niobium-tungsten liquid alloy in step 1 includes the following components in atomic content: Mo 30%-35%, Nb 30%-35%, W 30%-35%.

3. The method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy according to claim 1, characterized in that: The grain morphology of the columnar crystal structure alloy material in step 1 is one or more of columnar, blocky and ellipsoidal.

4. The method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy according to claim 1, characterized in that: The vacuum in step 2 is evacuated to a vacuum degree of 5.0×10 -3 Pa~5.0×10 -5 Pa, and the heating rate is 10°C / min to 20°C / min.

5. The method for regulating the columnar crystal structure characteristics of the rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy according to claim 1, characterized in that: The crucible in step 1 is a water-cooled copper crucible.

6. A method for regulating the columnar crystal structure characteristics of a rapidly solidified multi-principal element molybdenum-niobium-tungsten alloy according to claim 5, characterized in that: The initial temperature of the water-cooled copper crucible is 5°C to 20°C.